Application of Bionanomaterials in Tumor Immune Microenvironment Therapy - Jiawei Wang; Yan Bao; Yandan Yao (Journal of Immunology Research)
Targeted therapy for the cancer immune system has become a clinical reality with remarkable success. Immune checkpoint blockade therapy and chimeric antigen receptor T-cell (CAR-T) immunotherapy are clinically effective in a variety of cancers. However, the clinical utility of immunotherapy in cancer is limited by severe off-target toxicity, long processing time, limited efficacy, and extremely high cost. Bionanomaterials combined with these therapies address these issues by enhancing immune regulation, integrating the synergistic effects of different molecules, and, most importantly, targeting and manipulating immune cells within the tumor. In this review, we will summarize the most current researches on bionanomaterials for targeted regulation of tumor-associated macrophages, myeloid-derived suppressor cells, dendritic cells, T lymphocyte cells, and cancer-associated fibroblasts and summarize the prospects and challenges of cell-targeted therapy and clinical translational potential in a tumor immune microenvironment in cancer treatment.